Caracterização química e avaliação biológica do óleo essencial de Nectandra megapotamica (Spreng.) Mez - Amaral, Lúcio de Paula (2014)
Nectandra megapotamica (Lauraceae) is abundant in the Deciduos Forest in Santa Maria-RS. Its essential oil (EO) has been studied for biological activities due to its anti-inflammatory, antifungal, antimicrobial, and cytotoxic effects against tumor cells, among others. The presence of phenylpropanoids as well as sedative and anesthetic activities in R. quelen were observed in the prospect of EO of Nectandra megapotamica. As a hypothesis, we considered the seasonal variability and the occurrence of chemical phenotypes for the individuals in the same population of the species with different biological activities for the EO. The objectives of this study were to define the potential of N. megapotamica in a population in Santa Maria-RS for the production of EO; to determine the yield (Y), chemical composition and the seasonal variation of EO; to evaluate the possible occurrence of chemical phenotypes (differentiated chemical composition); to isolate compounds of interest; and to perform tests of biological activities for the EO and for the isolated compound. The EO samples were obtained from fresh leaves, which were initially separated in young (YL) and old leaves (OL) by hydrodistillation in triplicate for three hours. The collections occurred in function of the seasons in two locations in Santa Maria-RS (Morro do Elefante, and in the proximity of the 318 km of BR 158). The respective Y values were determined, and EO samples were analyzed by GC/MS. Some samples were also analyzed by GC-FID, in triplicate. The chemical composition of the EO was analyzed and grouped by multivariate techniques, main components and hierarchical grouping. The EO was also fractionated by CC, for the isolation of a compound, whose identification happened by NMR. The discrepant groups (CG2 and CG5) were tested for allelopathic, insecticide and anesthetic activities in fish. The compound obtained from CG5 was identified as isoelemicin (phenylpropanoid) and also tested for the anesthetic activity. The largest Y for the EO was observed in spring (YL 0.24% and OL 0.14%) during flowering, fruiting and foliation, and the lowest in autumn (YL 0.13% and OL 0.11%) in the rustification and at rest. The major constituents were α-pinene with greater Y in spring and summer (YL 30.81% and OL 35.86%), and bicyclogermacrene with greater Y in autumn and winter (YL 24.19% and OL 21.73%), which formed two large CG. In the CG of bicyclogermacrene, the presence of phenylpropanoids was observed and therefore it constituted a specific group (CG5). However, CG2 presented higher concentration of monoterpenoids. In the biological tests, the allelopathic activity (lower seed germination and seedling development) for L. sativa var. regina, B. subalternans, G. max, A. strigosa, L. multiflorum and O. sativa was observed when the seeds were submitted to the EO. Moreover, the insecticidal activity was observed in N. viridula, and also sedation in R. quelen. The CG5 was superior than CG2, concerning allelopathy in O. sativa; however, both groups were active at the concentration of 15% EO for the other species, which inhibits 100% germination of B. subalternans (QG5) and A. strigosa (both groups). Regarding the insecticidal action of EO at 5%, the CG5 promoted 46.67% mortality of N. viridula, and CG2 only 14.44%. Concering R. quelen, we observed toxicity associated with sedation, both by the EO similar to CG5 and by isoelimicin. The stage of anesthesia was observed at the concentracion of 500 mg L-1 EO; however, the effect was lower than that observed for eugenol (positive control). In conclusion, the species in the population assessed has the potential to produce EO as a source of new bioactive molecules and biological action mechanisms that should consider the toxicity component, which requires further studies.